Epigenetic therapy of hematological malignancies: where are we now?. (April 2013) - Popovic, Relja; Shah, Mrinal Y.; Licht, Jonathan D.
A growing amount of evidence points towards alterations in epigenetic machinery as a leading cause in disease initiation and progression. Like genetic alterations, misregulation of the epigenetic regulators can lead to abnormal gene expression. However, unlike genetic events, the epigenetic machinery may be targeted pharmacologically, potentially resulting in the reversal of a particular epigenetic state. The success of DNA methyltransferase and histone deacetylase inhibitors represents a proof of concept for the use of therapies intended to target the epigenome in the treatment of hematological malignancies. Nevertheless, the molecular mechanisms underlying the efficacy of these agents have not been completely elucidated. Recently, a large number of studies sequencing cancer cell genomes identified recurring mutations of epigenetic regulators, providing new insights into the molecular underpinnings of cancer. Consequently, the efforts to identify specific epigenetic inhibitors have been expanded in order to target particular subsets of patients. This review will summarize the progress made using the currently available epigenetic therapies and discuss some of the more recently identified targets whose inhibition may present potential avenues for the treatment of hematologic malignancies.